Five-year results of the peer assessment program of the College of Physicians and Surgeons of Ontario. - McAuley, R G (1990)
The office practices of 918 physicians selected through stratified random sampling from the College of Physicians and Surgeons of Ontario (CPSO) registry were assessed by peers and the Peer Assessment Committee of the CPSO from 1981 to 1985. The sample comprised 662 general practitioners (GPs) and family physicians (FPs) and 256 specialists in 11 fields. Of the physicians 749 (82%) had neither deficient records nor an unsatisfactory level of patient care. Of the GPs and FPs 97 (15%) had serious deficiencies in one or both areas, as compared with 4 (2%) of the specialists (p2 less than 0.00001). The proportions of certificants of the Royal College of Physicians and Surgeons of Canada and of the College of Family Physicians of Canada (CFPC) with serious deficiencies were low (2% and 3% respectively). Three statistically significant predictors of physician performance were found among the GPs and FPs: age, CFPC membership status and type of practice. Of the 56 physicians who were reassessed 6 to 12 months later 29 (52%) had made the improvements recommended by the committee. Our findings demonstrate the need, feasibility and acceptance of a peer assessment program of office practices in Ontario.